Strategi Pembelajaran Active Learning untuk Mengembangkan Kreativitas Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam - Chauzarani Rozaki; Muhammad Husnur Rofiq; Muhammad Anas Maarif (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2019)
The purpose of this paper is to analyze the importance of using an active learning strategy to implement Islamic Cultural History material so that students do not get bored. This paper uses library research by analyzing existing content with journals and books relevant to the theme. The results of this research are: Active learning in the material of Islamic Cultural History can take advantage of the mind mapping strategy containing a series of activities that aim to help unleash all the potential that students have to be maximized and can help students develop their creativity actively and happily. With the creativity possessed by participants, it can help students solve problems and help students improve understanding more easily understood by students and help improve student achievement.